PROPOSED BUSINESS STRATEGY OF HEALTHCARE IVD DISTRIBUTOR POST COVID 19 PANDEMIC ( CASE STUDY OF PT. SINERGY DIAGNOSTIC) - Khoerun F M, Mirza
PT. Sinergy Diagnostic has been a distributor of In Vitro Diagnostics (IVD) for over 17 years and has served several clients including medical laboratories, clinics, hospitals, and public institutions owned by both private and government entities effectively demonstrating the strategic implementation of Operations Cooperation (KSO). In the midst of the pandemic, the company witnessed a significant increase in sales of Point of Care Testing (POCT), which can be attributed to increased demand for rapid diagnostic tests. However, since the epidemic ended, the need for POCT is expected to decrease, representing a potential threat to the sales revenue of the company, which has become increasingly dependent on this category throughout the pandemian period. The research objectives are to conduct a business environment analysis to determine the current state and potential growth and strategically adapt to the changing dynamics of the In Vitro Diagnostic (IVD) sector post the COVID-19 pandemic. The study utilizes a combination of primary and secondary data resources. Primary data is collected through firsthand interviews and observations. Secondary data gathered from many sources such as books, papers, and academic journals that are pertinent to the in-vitro diagnostic (IVD) industry and marketing strategy. This aids in establishing a fundamental comprehension of the company's historical achievements and the determinants that impacted them. Subsequently, the analysis of the STP Analysis obtained results from 4 market segments including Hospital Type A, B-C, D-Puskesmas, and Private Laboratory. External environment is conducted using PEST analysis, Market Overview, Customer Analysis with qualitative descriptive using firmographic method using 15 sample of data including 3 Segments. These approaches provide insight into the larger macro-environmental factors that influence the IVD business and PT Sinergy Diagnostic's position within it. This is a comprehensive overview of the strategic position of PT Sinergy Diagnostic. From this perspective, a Strategy Formulation is carried out by employing the TOWS Matrix to delineate viable strategic measures for the organization. Furthermore, a novel suggested Business Transformation Plan is recognized, the result of this study Based on the overall analysis, PT Sinergy Diagnostic is still lagging behind other competitors. In order to remain competitive, PT Sinergy Diagnostic must adjust both in terms of resources and promotion used is Parity strategy, within the context of Porter's framework, often relates to competitive parity. While it doesn't necessarily mean being the absolute leader in every aspect, achieving parity is essential for survival and relevance in the marketplace. The subsequent marketing strategy being presented is the 7P's Marketing Mix. Certain aspects of the Marketing Mix are enhanced, while others are altered. The product and promotion were modified. Meanwhile, there were notable improvements in the Place, Physical Evidence, People, and Process.